2006
DOI: 10.1016/j.icesjms.2005.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Target strength of the lanternfish, Stenobrachius leucopsarus (family Myctophidae), a fish without an airbladder, measured in the Bering Sea

Abstract: This paper reports theoretical values of target strength (TS) for the lanternfish Stenobrachius leucopsarus, a fish without an airbladder, which dominates the Subarctic marine mesopelagic fish community. Two models for liquid-like slender bodies, the general prolate-spheroid model (PSM) and the deformed-cylinder model (DCM), were used to compute the TS of the fish relative to its orientation. The relative mass density g and the sound speed h in seawater were measured and used in both models. To confirm the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…However, acoustic methods are considered more reliable for biomass estimation. Some studies using acoustic surveys like High Sonar multibeams and Acoustics Doppler Current Profiler (ADCP) showed that trawl biomass usually did not match the acoustic data (Benoit-Bird et al 2001Yasuma et al 2006). A reason could be that the fishes showed net avoidance by detecting the gear visually or by sensing turbulence in water.…”
Section: Methods Of Biomass Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, acoustic methods are considered more reliable for biomass estimation. Some studies using acoustic surveys like High Sonar multibeams and Acoustics Doppler Current Profiler (ADCP) showed that trawl biomass usually did not match the acoustic data (Benoit-Bird et al 2001Yasuma et al 2006). A reason could be that the fishes showed net avoidance by detecting the gear visually or by sensing turbulence in water.…”
Section: Methods Of Biomass Estimationmentioning
confidence: 99%
“…Survey in the western Indian Ocean estimated the presence of 97 species of myctophids belonging to 23 genera (Nafpaktitis 1982). Stenobrachius leucopsarus is one of the abundant and dominant non-airbladder lanternfish in the Subarctic Pacific including the Bering Sea and Sea of Okhotsk (Yasuma et al 2006). Around 43 species belonging to 16 genera were recorded potentially in the southern ocean, out of which 7 species: Electrona antarctica, Gymnoscopelus braueri, G. ophisthopetrus, G. nicholski, Krefftichthys anderssoni, Protomyctophum bolini and P. tensioni were considered true representatives of regions of south of the Antarctic Polar Front (Hulley 1985;Kozlov 1995).…”
Section: Worldwide Distribution and Occurrencementioning
confidence: 99%
“…A density-bottle method [12,14,21] was used for measuring body-mass density. In this method, body-mass density was determined by evaluating the buoyancy of each specimen.…”
Section: Methodsmentioning
confidence: 99%
“…Yasuma et al [21]. The mass density of seawater (ρ sw ) was calculated as a function of mean temperature, salinity, and pressure [22] that observed depth range where the net tows were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the class of models developed for fluidlike zooplankton have been applied to predict the scattering from a variety of animals with fluidlike, weakly-scattering material properties, such as squid, fish without swimbladders, and other gelatinous zooplankton (Brierley et al, 2004;Kang et al, 2006;Warren and Smith, 2007;Wiebe et al, 2010;Yasuma et al, 2006Yasuma et al, , 2010. However, direct application of existing models should be treated with caution, since the scattering from any given animal may be strongly influenced by taxon-specific organs or structures.…”
Section: Scattering Modelsmentioning
confidence: 99%